Advances in Environmental Applied Physics - Caridi, Francesco (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
This Special Issue, "Advances in Environmental Applied Physics", collected original papers from eminent researchers in the field of environmental pollutants, which constitute a health risk to the population, increasing the likelihood of incurring cancer.